2022
DOI: 10.1111/camh.12626
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support on the relationships between internet use and sleep problems in adolescents during COVID‐19 pandemic: a multicentre study

Abstract: Background: This study examines the frequency of problematic internet use and sleep problems in adolescents aged 14-18 years during the COVID-19 pandemic and identifies the impact of factors such as sociodemographic characteristics, internet habits, changes in daily life, and perceived social support on these problems. Methods: This multicentre study was a questionnaire-based online survey study. The questionnaire included the Young Internet Addiction Scale, the Pittsburgh Sleep Quality Index, and the Multidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This could be partially viewed as a potentially problematic use of the internet. Orhon et al [32] found that problematic internet use among adolescents during the pandemic was associated with poorer sleep quality. Lower psychosocial functioning, such as a lack of physical activity, reduced academic performance, and problematic relationships with parents, were identified as predictors.…”
Section: Changes In Psychosocial Functioning During the Covid-19 Pand...mentioning
confidence: 99%
“…This could be partially viewed as a potentially problematic use of the internet. Orhon et al [32] found that problematic internet use among adolescents during the pandemic was associated with poorer sleep quality. Lower psychosocial functioning, such as a lack of physical activity, reduced academic performance, and problematic relationships with parents, were identified as predictors.…”
Section: Changes In Psychosocial Functioning During the Covid-19 Pand...mentioning
confidence: 99%
“…This could be partially viewed as a potentially problematic use of the internet. Orhon et al [36] found that problematic internet use among adolescents during the pandemic was associated with poorer sleep quality. Lower psychosocial functioning, such as a lack of physical activity, reduced academic performance, and problematic relationships with parents, were identified as predictors.…”
Section: Changes In Psychosocial Functioning During the Covid-19 Pand...mentioning
confidence: 99%